2002
DOI: 10.1590/s0021-75572002000200008
|View full text |Cite
|
Sign up to set email alerts
|

S. pneumoniae isolados da nasofaringe de crianças sadias e com pneumonia: taxa de colonização e suscetibilidade aos antimicrobianos

Abstract: Pneumococcal carriage rate was higher in healthy children than in children with pneumonia. Penicillin and cotrimoxazole resistance rates were high, especially among those attending day-care centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
3
24

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 11 publications
3
16
3
24
Order By: Relevance
“…8,4,[10][11][12] Of this study, seven (54%) of the 13 children less than 2 years old had suffered IPD due to SpNSPn. It is possible that this high level of penicillin resistance is partially due to the fact that HIV+ patients are often given antimicrobial treatment.…”
Section: %mentioning
confidence: 72%
See 1 more Smart Citation
“…8,4,[10][11][12] Of this study, seven (54%) of the 13 children less than 2 years old had suffered IPD due to SpNSPn. It is possible that this high level of penicillin resistance is partially due to the fact that HIV+ patients are often given antimicrobial treatment.…”
Section: %mentioning
confidence: 72%
“…The majority of these refer to colonization of the airways by Sp, since the difficulties in isolating the bacteria from cultures from people with pneumonia are well known. 4,[9][10][11][12][13] The only study published in Brazil on Sp serotypes identified from HIV+ children demonstrated that nasopharyngeal colonization of 112 children was no greater than that described in the literature for healthy children. 3 In our study, serotype 14 was the most frequent (four cases) and was also the serotype that exhibited greatest resistance to penicillin, which confirms data published in Brazilian literature.…”
Section: Resultsmentioning
confidence: 92%
“…Rey et al 15 , em estudo realizado em Fortaleza (CE), em 1998, determinaram a prevalência de colonização de nasofaringe em crianças sadias, admitidas em postos de vacinação, crianças de creches e crianças com pneumonia. No grupo de crianças sadias recrutadas em postos de vacinação, a prevalência de colonização de nasofaringe pelo pneumococo foi de 49%, enquanto no grupo de crianças de creches, a prevalência foi muito mais alta (72%).…”
Section: Discussionunclassified
“…Como ambos os grupos foram submetidos à coleta pela mesma técnica, no mesmo período, ficou claro que a freqüência à creche é um fator de risco para colonização. No entanto, mesmo considerando-se que o material foi obtido de nasofaringe, os resultados do estudo de Rey et al 15 mostram que a prevalência de colonização em Fortaleza é muito mais alta do que a encontrada em Taubaté, deixando clara a variação da prevalência de colonização em diversas regiões geográ-ficas.…”
Section: Discussionunclassified
“…4 In Brazil, 30% of children under two are colonized with S. pneumoniae. 1,4,10,21 The rate of pneumococcal nasopharyngeal colonization (PNC) in infants attending child day care centers is about 60%. 17 A recent study showed that children exposed to smoking were more likely to have their nasopharynx colonized with acute middle ear infection pathogens (Moraxella catarrhalis, Haemophilus influenzae, and pneumococcus).…”
mentioning
confidence: 99%